Padrões e fatores associados as incapacidades físicas em sujeitos em pós-alta da poliquimioterapia (PQT) para hanseníase, no município de Vitória da Conquista-BA, no período de 2001-2014 - Reis, Martha Cerqueira (2017)
Leprosy may lead to the development of physical disabilities and deformities, causing stigma associated with the disease. The aim of this study was to characterize the pattern of physical disabilities and associated sociodemographic and clinical factors in individuals who had completed multidrug therapy (MDT) for leprosy in the city of Vitória da Conquista, Bahia/Brazil, from 2001 to 2014. A cross-sectional study was performed, including 222 individuals after release from MDT. Physical disabilities were assessed applying the World Health Organization (WHO) disability grading (DG) and eyes-hands-feet score. The prevalence of any physical disabilities (DG1/DG2) after release from MDT was 64,8% (144), with 17,1% (38) DG2 cases. At the time of diagnosis and discharge by cure, 52,2% (116) and 65,3% (145) cases were not evaluated for DG, respectively. The most commonly affected body parts included the feet (56,7% - 126), followed by the eyes (26,1% - 58) and hands (25,2% - 56). There was worsening of DG in 32,1% (34) of cases (from diagnosis to discharge) but none of the variables studied showed significant association with worsening. The presence of physical disabilities was associated with illiteracy (RR = 1,27, 95% CI = 1,05 - 1.54), multibacillary classification (RR = 1,26, 95% CI = 1,008 – 1,574), occurrence of leprosy reactions (RR = 1,41, 95% CI = 1,14-1,74), and the presence of neural pain/enlarged nerve trunks (RR = 1,3, 95% CI = 1,02-1,64). Similarly, DG2 was associated with multibacillary classification (RR = 2,09, 95% CI = 1,007 – 4,366), occurrence of leprosy reactions (RP = 2,08, 95% CI = 1,08-3,99), and neural pain/enlarged nerve trunks (RR = 2,66, 95% CI = 1,16 – 6,09). Physical disabilities constitute an important problem for affected individuals and vulnerable groups after release from MDT, evidencing the need for intensive longitudinal monitoring and surveillance, in order to prevent specific leprosy-related sequels.